Metazoan parasites of fish species from Lake Gala (Edirne, Turkey) - (:unkn) unknown (My University, 2014)
Türkiye'nin kuzey-batısında yer alan öytrofik özellikteki Gala Gölü balıklarının parazitleri bilinmemektedir, bu nedenle araştırmamızda gölde bulunan balıkların metazoan parazitleri araştırılmıştır. Temmuz 2010 ve Haziran 2011 tarihleri arasında Gala Gölü'nde bulunan 16 balık türünden toplam 497 örnekle çalışıldı. Bu balıklarda 53 metazoan parazit türü teşhis edildi. Bu parazitlerden 32 Monogenea, 4 Cestoda, 7 Digenea, 4 Acanthocephala, 3 Nematoda, 2 Copepoda ve 1 Mollusca (glochidia) türü kaydedildi. Gala Gölü'nde incelenen balıkların parazit topluluğunun yapısı %34.0 endoparazit ve %66.0 ektoparazitlerden oluşmaktadır. Çalışılan tüm balık türlerindeki en yaygın parazit türleri; monogenean türler, Diplostomum spp., Tylodelphys clavata ve glochidia larvasıdır. Monogenean türlerle en yüksek enfeksiyon yüzdesi Rutilus rutilus'ta (%77.0) bulundu, Diplostomum spp. en yüksek yaygınlıkla Abramis brama'da (%100) görüldü. En çok sayıda parazit türü, 10 türle Abramis brama'da ve dokuz türle Carassius gibelio'da bulundu. Bu makale Gala Gölü'ndeki balıkların parazitleriyle ilgili ilk çalışmadır

Eutrophic Lake Gala, located in the north-west of Turkey, fish parasites of the lake are unknown; therefore, in the present investigation the metazoan parasites of the resident fish were examined. A total of 497 specimens of 16 fish species inhabiting Lake Gala were examined between July 2010 and June 2011. In or on these fish, 53 metazoan parasite species were identified. From these parasites, 32 species of Monogenea, four species of Cestoda, seven species of Digenea, four species of Acanthocephala, three species of Nematoda, two species of Copepoda and one species of Mollusca (glochidia) were recorded. The parasite community structure of the examined fishes from Lake Gala was made up of 34.0% endoparasites and 66.0% ectoparasites. Monogenean species, Diplostomum spp., Tylodelphys clavata and glochidia larvae were the most prevalent parasite species in all the fish hosts examined. The highest prevalence of infection with monogenean species was found in Rutilus rutilus (prevalence 77.0%); Diplostomum spp. occurred with the highest prevalence (100%) in Abramis brama. The largest numbers of parasites species were found in Abramis brama (10 species) and Carassius gibelio (nine species). This paper represents the first study of parasites of the fishes in Lake Gala
Gala Gölü (Edirne)’ ndeki balık türlerinin metazoan parazitleri
Keywords: Balıkçılık; Zooloji